OP0105 Improving the Effectiveness of Exercise Therapy for Older Adults with Knee Osteoarthritis: A Pragmatic Randomised Controlled Trial (The Beep Trial). (9th June 2015) - Foster, N.; Nicholls, E.; Holden, M.; Healey, E.L.; Kigozi, J.; Jowett, S.; Tooth, S.; Hay, E.M.
Abstract : Background: Exercise for osteoarthritis (OA) is recommended as a core treatment but we currently don't know whether changing the characteristics of exercise improves patients' outcomes. Objectives: To determine whether altering physiotherapy-led exercise programmes can improve outcomes for older adults with knee OA. Methods: The BEEP trial was a randomised controlled trial (ISRCTN93634563 ) investigating the effectiveness of two physiotherapy-led exercise interventions compared with Usual Physiotherapy Care (UPC), for pain and function in older adults with knee pain. 65 general practices and 5 NHS physiotherapy services recruited adults aged ≥45 years with knee OA who were randomised to 1 of 3 interventions. These included: UPC, up to 4 sessions of advice and exercise over 12 weeks; Individually Tailored Exercise (ITE), an individualised, supervised and progressed lower limb exercise programme in 6 to 8 sessions over 12 weeks; or Targeted Exercise Adherence (TEA), transitioning from lower limb exercise to general physical activity in 8 to 10 contacts over 6 months. 47 physiotherapists delivered the interventions; 15 UPC, 17 ITE and 15 TEA. Primary outcomes were pain and function measured by the WOMAC at 6 months. A range of secondary outcomes was measured at 0, 3, 6, 9 and 18 months. An economic evaluation was conducted at 18 months using data collected on quality-adjusted life years (QALYs) and knee OA related resource use. Blinding of participants and physiotherapists wasn't possible, but data collection and analyses were conducted blind to allocation. Analysis was by intention-to-treat Results: 514 adults with knee OA were randomised and 87% provided primary outcome data at 6 months. There were no clinically or statistically significant differences between groups at 6 months (UPC mean (SD) WOMAC pain 6.4 (4.0) and function 21.4 (14.1); ITE pain 6.4 (4.0) and function 22.3 (13.7); TEA pain 6.2 (3.8) and function 21.5 (13.2)) or at any other time-point. On average, all participants improved during treatment and the benefits of treatment were fairly stable over 18 months. At 6 months, 50%, 51% and 55% were categorised as treatment responders in UPC, ITE and TEA respectively. Self-reported exercise adherence was high at 3 months in all groups (UC 75%, ITE 81%, TEA 81%) but remained higher for longer in the TEA group at 6 months (UPC 55%, ITE 68% and TEA 77%). The economic evaluation suggested that UPC was the most cost-effective intervention with lower costs (UPC £383, ITE £656, TEA £524) and higher QALYs (UPC 1.035, ITE 1.020, TEA 1.032). Conclusions: Changing the characteristics of exercise programmes for older adults with knee OA did not improve pain and function compared to UPC. UPC was found to be cost-effective and should be an attractive option to policy-makers. Clearer identification of those who respond to exercise, rather than changing the characteristics of exercise programmes, is needed in future research. Acknowledgements: This paper presents independent research funded by the National Institute for Health Research (NIHR) (Number: RP-PG-0407-10386) and an NIHR Research Professorship (NIHR-RP-011-015). The views expressed in this publication are those of the authors and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: None declared